Shivers: The Awful Apple Orchard - Spenser, M D (Peter Haddock Limited, 1998)
The local apple orchard near the place where Daniel and his sister Sara are vacationing, displays signs of being haunted. Both try to escape the weird happenings and find themselves in dangerous situations.
Keywords: Horror & Ghost Stories; Juvenile Fiction